Intrathecal synthesis of immunoglobulin G and Mycobacterium tuberculosis-specific humoral immune response in tuberculous meningitis. - Cho, T Y (1995)
Local synthesis of immunoglobulin G (IgG) in the central nervous system was investigated in 10 patients with tuberculous meningitis (TBM), 15 patients with aseptic meningitis (AM), and 15 patients with pulmonary tuberculosis only (PTBO). The IgG synthesis rate for patients with TBM was 56.4 +/- 18.9 mg/day (mean +/- standard deviation), which was significantly higher than that for patients with AM (8.0 +/- 6.7 mg/day, P < 0.001) and that for patients with PTBO (7.5 +/- 4.4 mg/day, P < 0.001). Therefore, the increased IgG synthesis rate in the central nervous system provided supporting evidence for differentiating the diagnosis of TBM from that of AM (sensitivity, 100%; specificity, 83.3%). Simultaneous measurement by enzyme-linked immunosorbent assay of IgG seroreactivity to lipoarabinomannan and purified protein derivative antigens in cerebrospinal fluid (CSF) demonstrated seropositivity in all 6 patients with TBM, 4 of 15 patients with AM, and 4 of 10 patients with PBTO. All patients showing false-positive reactivity in CSF demonstrated seropositivity in sera and normal ranges for IgG synthesis rates in CSF. Also, the semiquantitive measurement of IgG antibody (Ab) titers in these patients demonstrated higher IgG Ab titers in serum than in CSF except for one patient with a highly elevated albumin quotient, suggesting a leaky blood-brain barrier. The results strongly suggested that the Mycobacterium tuberculosis-specific IgG Abs were diffusible through the blood-brain barrier, which addresses the pitfall of serological tests for the early diagnosis of TBM. The serological detection of IgG Abs to lipoarabinomannan and purified protein derivative antigens in CSF could be misleading in the presence of simultaneously elevated of IgG Abs in serum.